Kinetics of physico-chemical degradation in mango cubes using traditional and high performance dehydration systems - Villarino, Blanca J. (2002)
The kinetics of browning and ascorbic acid destruction were studied in carabao mango cubes dehydrated using traditional and high-performance systems for the shelf life prediction of the products. Comparative analyses of the dehydration systems in terms of drying rates and product characteristics were done as well as the sorption isotherm profile of the products. Shelf life was estimated using the predictive models. For the 0.75 cm^3 mango cubes it took 8-12 hours to complete the dehydration process using the traditional system while for the high performance method it took 4 to 5 hours. High performance method resulted to faster drying rate and better product quality. Sorption isotherm determination of the finished products dehydrated using both the traditional and high performance methods have monolayer values ranging from 0.4 to 0.5. Browning developments in the products followed a zero-order of reaction. Rates of reaction for traditional method ranged from 0.002 to 0.012 absorbance per day while for high performance method it ranged from 0.001 to 0.008 absorbance per day. These resulted to 33.11and 24.73 Kcal/mole energies of activation using the rates of reaction for traditional and high performance methods, respectively. Products dehydrated using the high-performance system had a shorter shelf-life due to the effect of the moisture content and water activity during time of failure for color. as exhibited by the Ea of the browning reactions, the high performance method required lesser amount of energy for NEB to occur as it may also have depended on the water activity and moisture content of the samples. Q10 values for the products dehydrated using the traditional and high-performance systems were computed to be 3.11 and 2.61, respectively. The high performance method using the pilot static dryer gave a better alternative of dehydration in terms of the drying rate and product quality but shelf life study of the products upon storage did not give favorable results. However, manipulation of the dryer design for the high performance system, product formulation and packing materials can give very acceptable and stable finished products with export potential. This is highly beneficial to dried mango producers as they are given option of a new product along with new system of dehydration for dried mangoes.